Research progress on levoglucosan production via pyrolysis of lignocellulosic biomass and its effective recovery from bio-oil. Issue 4 (August 2021) - Hakeem, Ibrahim Gbolahan; Halder, Pobitra; Marzbali, Mojtaba Hedayati; Patel, Savankumar; Kundu, Sazal; Paz-Ferreiro, Jorge; Surapaneni, Aravind; Shah, Kalpit
Abstract: Production of high value biochemicals from lignocellulose biomass via pyrolysis, particularly levoglucosan (LG) has received immense attention in recent years. LG production via fast pyrolysis has recorded a continuous development over the past years, which demands a state-of-the-art review, covering the LG recovery methods and commercial feasibility analysis of the process. This paper provides an in-depth review of the progress and current status of bio-LG production with a focus on formation mechanisms, influential variables, recovery methods and techno-economic prospects. Based on the experimental findings of the previous studies, this review concluded that the LG yield from biomass via pyrolysis could be proposed as a function of biomass structural properties, cellulose content, inorganic minerals content as well as pyrolysis process conditions. An essential aspect of maximising the overall efficiency of LG production process is the adoption of efficient in-situ or post-pyrolysis LG extraction techniques, which has been critically reviewed for the first time. The paper also summarises the techno-commercial assessment studies of LG facility, highlighting the limiting factors towards the economic attractiveness of the process. Finally, the review highlights the knowledge gaps and provides future recommendations, which will be helpful for the improvement of productivity and economic feasibility of bio-LG production process. Graphical Abstract: ga1 Highlights: Levoglucosan (LG) production from lignocellulosic biomass via pyrolysis was reviewed. Effect of feed composition and pyrolysis process conditions on LG yield was studied. Removal/passivation of alkali and alkaline earth metals were reported. In-situ and post-pyrolysis extraction of LG from bio-oil were discussed. Techno-economic outlook of the pyrolytic LG production was explored.